Wajib Pajak dan Generasi Muda: Tax Morale Mahasiswa di Indonesia - Susila, Budi; Juniult, Partomuan T.; Hidayat, Asrul (Jurnal Ekonomi dan Pembangunan Indonesia, 2016)
This paper is aimed to investigate the level of tax morale on Indonesia college students regarding fulfillment of tax obligations as an indication of their characteristics as future taxpayers and the factors behind their tax morale. This research exercised a survey method with respondents from the University of Indonesia chosen with a random sampling technique. The results indicated that the level of tax morale on Indonesia college students is relatively good. As for the variables that influenced the tax morale are gender, religious observance, and the perception of the importance of the government.